PERAN UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES TENTANG PENGUNGSI LUAR NEGERI DI INDONESIA - Safitri, Dwi Rani; Zeinudin, Moh.; Anita, Anita; Sugiarti, Yayuk (2024)
Refugees are individuals or more who are forced to leave their home country due to circumstances that may lead to torture and so on. Indonesia did not participate in ratifying the 1951 convention and the 1967 Protocol. The Indonesian government cooperates with international institutions and international organizations UNHCR (United Nations High Commissioner for Refugees) is a global organization under the United Nations High Commissioner for Refugees, with its headquarters located in Geneva, Switzerland. On December 14, 1950, this organization was established with the aim of protecting and assisting refugees at the request of the government or the UN, and then assisting the refugees in the process of relocating to a new location.